2021
DOI: 10.1213/ane.0000000000005521
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of 6 Topical Pharmacological Agents for Preventive Interventions of Postoperative Sore Throat After Tracheal Intubation: A Systematic Review and Network Meta-analysis

Abstract: BACKGROUND: Topical pharmacological agents typically used to treat postoperative sore throat (POST) after tracheal intubation include nonsteroidal anti-inflammatory drugs (NSAIDs), corticosteroids, lidocaine, Glycyrrhiza (licorice), and N-methyl-d-aspartate (NMDA) receptor antagonists (including ketamine and magnesium). However, the optimal prophylactic drug remains elusive. METHODS: The literature published before September 8, 2019 was searched on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Lidocaine spray has proved NOT to decrease the intensity or presence of POST and can even be linked to worse outcomes [13]. The lidocaine's vehicle creates a film over the mucosa and prevents normal secretion.…”
Section: Lidocaine Spraymentioning
confidence: 99%
See 1 more Smart Citation
“…Lidocaine spray has proved NOT to decrease the intensity or presence of POST and can even be linked to worse outcomes [13]. The lidocaine's vehicle creates a film over the mucosa and prevents normal secretion.…”
Section: Lidocaine Spraymentioning
confidence: 99%
“…Magnesium has been shown to be more effective than ketamine to reduce the incidence and severity of POST [13,17] but has little clinical use due to the difficulty for preoperative nebulization as well as the added costs in both public and private settings since the equipment for nebulization is not generally necessary in a healthy patient undergoing surgery.…”
Section: Ndma Antagonistsmentioning
confidence: 99%
“…There are also many other ETT coatings that can be used to possibly decrease inflammation related symptoms such as sore throat or tracheitis. A systematic review done by Wang et al found that glycyrrhizin, corticosteroids, nonsteroidal anti‐inflammatory drugs (NSAIDs), and N ‐methyl‐d‐aspartate (NMDA) receptor antagonists (ketamine and magnesium) were associated with reduced postoperative pharyngeal pain 48 …”
Section: Medications and Anti‐inflammatory Response Therapiesmentioning
confidence: 99%
“…A systematic review done by Wang et al found that glycyrrhizin, corticosteroids, nonsteroidal anti-inflammatory drugs (NSAIDs), and N-methyl-d-aspartate (NMDA) receptor antagonists (ketamine and magnesium) were associated with reduced postoperative pharyngeal pain. 48 In a comparative study, it was established that the benzydamine hydrochloride gel on the ETT cuff is a simple and effective method that can significantly decrease the severity of postoperative sore throat compared with 10% lidocaine, 5% lidocaine, and normal saline. 49 However, in a subsequent study done by Yhim et al, it was concluded that application of prophylactic benzydamine hydrochloride spray to the vocal cords and upper trachea did not show a reduction in postoperative sore throat in the pediatric population.…”
Section: Infl Ammatory Re S P On S E Ther Apie Smentioning
confidence: 99%
“…Postoperative sore throat (POST) is a common consequence of general anesthesia after endotracheal intubation with an incidence varying from 15% to 64%. 7 , 8 The symptoms of POST include pain and discomfort, cough, hoarseness, and laryngitis, which may be the result of inflammation caused by mucosal damage during airway fixation. 9 , 10 Its etiology is believed to involve mucosal dehydration, trauma from tracheal intubation, and mucosal erosion caused by tracheal tube cuff pressure.…”
Section: Introductionmentioning
confidence: 99%